Key trends in news coverage of the 501 deportees from Australia in prominent Australian and New Zealand news media outlets : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, New Zealand - Mahadurage, Dineka (Massey University, 2022)
The Australian government introduced Section 501 of the Migration Act 1958 in December 2014, which has resulted in thousands of New Zealand citizens living in Australia on Special Category Visas being deported back to New Zealand. These deportations have become one of the most controversial migration issues between these countries; a controversy that has been played out across media outlets in both Australia and New Zealand. As news media still play a major role in public deliberations regarding contentious issues, there is a need to explore the exercise of symbolic power in how media frame this controversy in both countries. News coverage of the issue from 2015 to 2021 in Australia and New Zealand was collected to gain a sense of how the dominant narrative in each country developed over time, who the main stakeholders or characters afforded the right of appearance were, and what roles these characters played in various plotlines. A mixed method approach encompassing quantitative and qualitative content analyses was deployed to discern common trends in coverage for 2015 and 2021. The quantitative analysis identified percentages relating to stakeholders' representation and how 501 deportees and section 501 processes were portrayed as a percentage in the media. Using the qualitative method, the thesis also looked at key major events and overall evolving narratives related to the research topic. This then led to an examination on how 501 deportees were being positioned in news items as 'strangers' (in the George Simmel sense of the term) who did not belong in either Australia or New Zealand. Key findings demonstrate that the majority of news items were dominated by the voices of elites such as government officials, and the exercise of symbolic power promoted the perspectives of political leaders, who tended towards positioning 501 deportees outside the scope of justice. This thesis contributes to a growing body of literature demonstrating how migrant groups are often depicted in a negative light in countries such as Australia and New Zealand and increases understanding of discriminative practices in news media coverage.
Keywords: 470107 Media studies